Traumatic Endophthalmitis due to Cellulosimicrobium cellulans - Pimkwan Jaru-ampornpan; Anita Agarwal; Narinder K. Midha; Stephen J. Kim (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of traumatic endophthalmitis due to Cellulosimicrobium cellulans. Design. Case report. Methods. Retrospective chart review. Results. To our knowledge, this is the first report of traumatic endophthalmitis due to C. cellulans, which did not respond to intravitreal antibiotics or repeat vitrectomy and ultimately led to the discovery of an occult intraocular foreign body. Conclusions. C. cellulans is a rare cause of endophthalmitis. Greater awareness of this bacterium in the ophthalmic literature as a cause of endophthalmitis and its association with foreign bodies may allow earlier and more purposeful intervention in future cases.